Validation of ecologists in enterprise management system: a case study analysis - Shpak, Nestor; Dvulit, Zoriana; Maznyk, Liana; Mykytiuk, Oksana; Sroka, Włodzimierz (My University, 2019)
The article is devoted to the study of the influence of personnel validation on the efficiency of the enterprise management system. These components of validity, such as the accordance of a person's qualifications to the position occupied or applied for (vacancy profile), education by specialty and other characteristics of an individual labor supply, etc., are the key determinants in the selection of managers and contribute to the effective application of their specific management functions and the transformation of the latter through the management methods into effective management decisions. Confirmation of the certainty of such an impact are the results of applied research in the area of responsibility of environmental managers (for example, the dependence of the level of environmental safety of the enterprise on the validity of environmentalists). The management of railway transport enterprises (RTE) of the joint stock company "Ukrainska zaliznytsia" (JSC "Ukrzaliznytsia") was selected for analysis, the competence of which concerns the use of natural resources and environmental protection (environmentalists) as one of the components of sustainable development. The method of integrated assessment of the level of ecological safety is proposed based on the application of taxonomic analysis, which provides the opportunity to use a scenario approach to the development of situations taking into account the different levels of validity of RTE environmentalists. Стаття присвячена дослідженню впливу валідації персоналу на ефективність системи управління підприємством. Ці складові обґрунтованості, такі як відповідність кваліфікації особи займаній або претендованій посаді (профіль вакансії), освіта за спеціальністю та інші характеристики індивідуальної пропозиції робочої сили тощо, є ключовими детермінантами підбору керівників і сприяють ефективному застосуванню ними конкретних управлінських функцій і перетворенню останніх за допомогою методів управління в ефективні управлінські рішення. Підтвердженням достовірності такого впливу є результати прикладних досліджень у сфері відповідальності екологічних менеджерів (наприклад, залежність рівня екологічної безпеки підприємства від обґрунтованості екологів). Для аналізу обрано керівництво підприємств залізничного транспорту (ПЗТ) акціонерного товариства «Українська залізниця» (АТ «Укрзалізниця»), компетенція якого стосується використання природних ресурсів та охорони навколишнього середовища (екологи) як однієї зі складових сталого розвитку. Запропоновано методику комплексної оцінки рівня екологічної безпеки на основі застосування таксономічного аналізу, яка дає можливість використовувати сценарний підхід до розвитку ситуацій з урахуванням різних рівнів обґрунтованості РТЕ екологів.
Keywords: кафедра економіки праці та менеджменту; railway companies; environmental safety; сталий розвиток; залізничні компанії; залізничні компанії; валідація; валідація; екологічна безпека